Loss of Cep72 affects the morphology of spermatozoa in mice - Chen, Zhen; Xu, Yating; Ma, Dupeng; Li, Changrong; Yu, Ziqi; Liu, Cong; Jin, Tingyu; Du, Ziye; Li, Zejia; Sun, Qi; Xu, Yumin; Liu, Rong; et al. (Frontiers in Physiology, 2022)
The centrosome regulates mammalian meiosis by affecting recombination, synapsis, chromosome segregation and spermiogenesis. Cep72 is one of the critical components of the centrosome. However, the physiological role of Cep72 in spermatogenesis and fertility remains unclear. In this study, we identify Cep72 as a testis-specific expression protein. Although, Cep72 KO mice were viable and fertile, their sperms were morphologically abnormal morphologies with incomplete flagellum structures. Transcriptome analysis reveals significant differences in six genes (Gm49527, Hbb-bt, Hba-a2, Rps27a-ps2, Gm29647 and Gm8430), which were not previously associated with spermatogenesis. Overall, these results indicate that Cep72 participants in regulating sperm morphology, and yet is dispensable for fertility in mice.